Shape change analysis of tensegrity models - Oh,Chai Lian (2019)
Abstract This paper presents a computational strategy for shape change of tensegrity models to achieve the prescribed target coordinates of a set of monitored nodes via forced elongation of cables. Mathematical formulation for incremental equilibrium equations of a tensegrity model during the shape change analysis is derived and presented. An optimization approach in determining forced elongation of cables using sequential quadratic programming with defined inequality constraints is formulated and presented. Four tensegrity models namely the simplex, quadruplex, two-stage tensegrity model and tapered three-stage tensegrity model are tested using the proposed shape change algorithm. Capability of tensegrity models to undergo bending, axial, twisting deformation and combinations of these deformations is also described.